A dural arteriovenous fistula associated with an encephalocele presenting as otitis media with effusion. Issue 11 (16th October 2018) - Ahmed, W; Connor, S; Obholzer, R; Pai, I
Abstract: Objective: This case report illustrates an unusual case of a dural arteriovenous fistula and an associated encephalocele presenting as otitis media with effusion. Case report: A 53-year-old man presented with right-sided hearing loss and aural fullness of 2 years' duration. Examination revealed ipsilateral post-auricular pulsatile tenderness. Computed tomography showed transcalvarial channels suggestive of dural arteriovenous fistula. Further magnetic resonance imaging demonstrated the presence of a temporal encephalocele herniating through the tegmen tympani defect, as well as the abnormal vascularity. Angiography confirmed a Cognard type I dural arteriovenous fistula, which is being managed conservatively. Surgical repair of the encephalocele was recommended but declined by the patient. Conclusion: Dural arteriovenous fistula is an uncommon intracranial vascular malformation rarely seen by otolaryngologists, with pulsatile tinnitus being the usual presentation. To our knowledge, this is the first reported case of dural arteriovenous fistula presenting with conductive hearing loss and otalgia.